Imaging Recommendations for Diagnosis, Staging, and Management of Soft Tissue Sarcomas - Lupton, Kenneth; Salins, Manjusha; Pass, Bill; Negi, Raj; Gupta, Harun (Indian Journal of Medical and Paediatric Oncology, 2023)
Soft tissue lesions are a wide range of tumors of mesenchymal cell origin, occurring anywhere in the body with a vast number of histological subtypes both benign and malignant. These are common in clinical practice and vast majority are benign. This article focuses on soft tissue sarcoma of the trunk and extremities and discusses their imaging guidelines.
Keywords: human gammaherpesvirus 8; human immunodeficiency virus; MFS; soft tissue sarcoma